What can we learn from one-to-one trials in Instructional design? A case from module development - Muhsinah Annisa; Dasim Budimansyah; Mupid Hidayat; Atiek Winarti; Fadhlan Muchlas Abrori (Research and Development in Education (RaDEn), 2024)
The one-to-one trial phase within the instructional design development model has frequently been neglected in prior research. This stage should provide much in-depth insight considering its nature, which is in-depth face-to-face data collection between designers and participants. In this study, we aim to analyze a particular instance of module development during the one-to-one trial phase. This study is part of the media development stage with the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate) at the implementation stage. We used quantitative data collection through scoring and qualitative data through interviews with six participants involved in the one-to-one trial. The findings revealed that students provided critical feedback on two aspects of the module, particularly its design appeal and suitability for independent learning, aligning with an average participant score of 3 on a 1-5 scale. These results provide an overview that one-to-one as a foundation and initiation for a broader trial plays an essential role in providing a starting point for an implementation where quantitative and qualitative data provide holistic insight.